Gambaran Pengetahuan dan Sikap Akseptor Keluarga Berencana (Kb) terhadap Penggunaan Metode Suntik di Puskesmas Teling Atas Kota Manado - Siagian, Iyone E.T.; Lampus, Benny S.; Pijoh, Angel P.O. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2013)
Family Planning Program is one ofthe government's effortsin thesuppression ofthe populationinIndonesiathroughthe use ofcontraception. One typeof contraception thatattracted manyIndonesian people is contraceptive injection method. Data from Teling Atas Public Health Center also indicate that most widely family planning acceptors use contraceptive injection method. The objective of this research was to obtain the description of the knowledge and attitude of family planning acceptors on the use of injection method at Teling Atas Public Health Center Manado. This was a descriptive study using survey method. Samples taken were the family planning acceptors of injection methodwho visited the family planning clinic of Teling Atas Public Health Center during November-December 2012, which amounted to 50 people. The research instrument used was a questionnaire containing each 10 questions related to knowledge and attitude. Results showed that the knowledge offamily planning acceptorswere 54% goodand 46% less, andthe attitudeof family planning acceptorswere 82% goodand 18% less.Conclusion:Based on the results of this research, the knowledge and attitude of family planning acceptors on the use of injection method is mainly good. Keywords: attitude, family planning, family planning acceptors, injection method, knowledge